New natural protein tyrosine phosphatase 1B inhibitors from Gynostemma pentaphyllum - Xianting Wang; Yidan Deng; Jianmei Wang; Lin Qin; Yimei Du; Qianru Zhang; Di Wu; Xingdong Wu; Jian Xie; Yuqi He; Daopeng Tan (Taylor & Francis Group, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease mainly caused by insulin resistance, which can lead to a series of complications such as cardiovascular disease, retinopathy, and its typical clinical symptom is hyperglycaemia. Glucosidase inhibitors, including Acarbose, Miglitol, are commonly used in the clinical treatment of hypoglycaemia. In addition, Protein tyrosine phosphatase 1B (PTP1B) is also an important promising target for the treatment of T2DM. Gynostemma pentaphyllum is a well-known oriental traditional medicinal herbal plant, and has many beneficial effects on glucose and lipid metabolism. In the present study, three new and nine known dammarane triterpenoids isolated from G. pentaphyllum, and their structures were elucidated by spectroscopic methods including HR-ESI-MS,1H and 13C NMR and X-ray crystallography. All these compounds were evaluated for inhibitory activity against α-glucosidase, α-amylase and PTP1B. The results suggested that compounds 7∼10 were potential antidiabetic agents with significantly inhibition activity against PTP1B in a dose-dependent manner.